Đầu tư công nghệ và sự ổn định của hệ thống ngân hàng Việt Nam - Trần Thị Thanh, Nga; Phạm Khánh, Duy; Lê Vũ Linh, Toàn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Banking stability is a critical issue that has received a host of interest from researchers, regulators, and policymakers over the years. However, the impact of the information technology (IT) trend, which is recently fast improving on a global scale, on banks’ stability has not yet been adequately investigated. This study examines the nexus of IT investment on bank stability based on balanced panel data from Vietnam, a bank-based emerging economy, between 2010 and 2020. Using the SGMM method, this paper suggests that IT expenditure can improve banks’ stability in general. Moreover, the results also show that technology investment increases the stability of large banks, however, it also pushes small banks to more instability.
Keywords: Information Technolog; Financial Stability; Bank Performance; GMM; Vietnam; Emerging Market